Two‐week inhalation of budesonide increases muscle Na, K ATPase content but not endurance in response to terbutaline in men. (7th April 2016) - Hostrup, M.; Jessen, S.; Onslev, J.; Clausen, T.; Porsbjerg, C.
Abstract : While chronic systemic administration of glucocorticoids increases muscle Na +, K + ATPase content, such effect is unexplored after therapeutic inhalation. We investigated the effect of therapeutic inhalation of the glucocorticoid budesonide on Na +, K + ATPase content of skeletal muscle in men. Ten healthy trained subjects, aged 23 ± 4 years (mean ± 95% CI), participated in the study. Before and after 2 weeks of daily inhalation of budesonide (1.6 mg/day), a biopsy was taken from the vastus lateralis muscle for measurement of Na +, K + ATPase content and blood samples were drawn for determination of plasma budesonide, cortisol, and K + . Subjects' performance during cycling to fatigue at 90% of incremental peak power output (iPPO) was measured in response to 4 mg inhaled terbutaline to maximally stimulate Na +, K + ATPase activity. Plasma concentrations of budesonide rose to 5.0 ± 1.6 nM with the intervention, whereas no changes were observed in plasma cortisol. Muscle Na +, K + ATPase content increased ( P  ≤ 0.01) by 46 ± 34 pmol/(g wet wt) (17% increase) with the intervention. Cycling performance at 90% of iPPO did not change ( P  = 0.21) with the intervention (203 vs 214 s) in response to terbutaline. The present observations show that therapeutic inhalation of glucocorticoids increases muscle Na +, K + ATPase content, but does not enhance high‐intensity cycling endurance in response to terbutaline.